Биологическая характеристика опухолевых клеток больных острой миелоидной лейкемией - Исакова, Л.М.; Дранник, Г.Н.; Гордиенко, А.И.; Третяк, Н.Н. (Видавничий дім "Академперіодика" НАН України, 2007)
It is revealed that, in patients with AML, the amount of CD80+ CD33+, CD86+CD33+ monocytes is higher in remission than in the first acute period. This testifies to the activation of mechanisms of control over the expression of costimulatory molecules. It is shown that the duration of the first remission increases at a simultaneous expression of molecules CD80+, CD86+ on CD33+ monocytes of peripheric blood. Restoration of parameters of the T-system of immunity (CD3+ CD28+, CD4+, CD8+ lymphocytes) in patients with AML in a period of remission is revealed.